2014
DOI: 10.3892/ijmm.2014.2012
|View full text |Cite
|
Sign up to set email alerts
|

Centipedegrass extract induces apoptosis through the activation of caspases and the downregulation of PI3K/AKT and MAPK phosphorylation in leukemia cells

Abstract: Acute lymphoblastic leukemia (ALL), which involves the blood and bone marrow, is the most common type of cancer in children younger than 5 years of age. Previous studies have investigated the effects of centipedegrass extract (CGE), which is mainly composed of maysin and its derivatives, and have demonstrated that it has various biological activities, including antioxidant and anti‑inflammatory activities, pancreatic lipase inhibitory activity, anti-adipogenic activity and insecticidal activity. To the best of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Furthermore, we also examined the effects of boehmenan on Akt/70S6 pathway activation, which is an important oncogenic signaling pathway involving growth and migration of cancer cells. 20 As shown in Figure5A to C , Western blot results revealed that boehmenan concentration-dependently inhibited EGF-induced 70S6 and S6 phosphorylation, but did not affect the Akt phosphorylation.…”
Section: Resultsmentioning
confidence: 73%
“…Furthermore, we also examined the effects of boehmenan on Akt/70S6 pathway activation, which is an important oncogenic signaling pathway involving growth and migration of cancer cells. 20 As shown in Figure5A to C , Western blot results revealed that boehmenan concentration-dependently inhibited EGF-induced 70S6 and S6 phosphorylation, but did not affect the Akt phosphorylation.…”
Section: Resultsmentioning
confidence: 73%
“…It has been shown that thyme essential oil significantly regulates interferon signaling, N-glycan biosynthesis and ERK5 signaling [ 26 ]. Therefore, it has been thought that activated AKT and ERK can function as key effectors of the PI3K and MAPK signaling pathways to promote cell survival and proliferation [ 32 ]. ERK1/2 has previously been evidenced to be able of inhibiting the apoptosis effector molecule caspase-3 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis deficiency may be involved in cancer initiation, progression and treatment failure in cancers with MDR (19). Apoptosis is regulated at multiple levels in the extrinsic and intrinsic pathways (20). The extrinsic pathway involves death receptors on the cell surface that can directly activate caspase-8.…”
Section: Discussionmentioning
confidence: 99%